EXPLORING THE IMPACT OF MENTAL BOUNDARIES: STRESS PERCEPTION IN THICK VS. THIN BOUNDARIES - Choudhary, Vaishali (LIFE: International Journal of Health and Life-Sciences, 2024)
This study investigates the influence of mental boundaries, a personality dimension rooted in early psychological concepts, on the perceived stress levels of college students. Mental boundaries have been recognized as a barrier protecting against traumatic events (Harrison & Singer, 2014) and offer an intriguing avenue to explore differences in stress perception based on boundary thickness. The aim of this research is to assess the effect of thick and thin mental boundaries on perceived stress among undergraduate college students. A sample of 150 students was surveyed, using the Perceived Stress Scale (PSS) developed by Sheldon Cohen and the BQ-sh by David Rawlings. Results indicate that perceived stress was significantly higher among 3rd year students. Gender differences were observed, with female students exhibiting thinner mental boundaries compared to their male counterparts. Students with higher scores on PSS were found to correlate with specific BQ-sh Sub-scales, including the need for order, sensitivity, and trust, while displaying lower scores on childlikeness and perceived competence. In conclusion, this study empirically establishes the impact of mental boundaries as a personality dimension on college student’s stress perception. Furthermore, it advocates for a renewed focus on mental boundaries within research as a personality dimension.